Inhibition of T-antigen expression promoting glycogen synthase kinase 3 impairs merkel cell carcinoma cell growth. (1st January 2022) - Houben, Roland; Hesbacher, Sonja; Sarma, Bhavishya; Schulte, Carolin; Sarosi, Eva-Maria; Popp, Sabine; Adam, Christian; Kervarrec, Thibault; Schrama, David
Abstract: Merkel cell carcinoma is an aggressive skin cancer frequently caused by the Merkel cell polyomavirus (MCPyV). Since proliferation of MCPyV-positive MCC tumor cells strictly depends on expression of the virus-encoded T antigens (TA), these proteins theoretically represent ideal targets for different kinds of therapeutic approaches. Here we developed a cell-based assay to identify compounds which specifically inhibit growth of MCC cells by repressing TA expression. Applying this technique we screened a kinase inhibitor library and identified six compounds targeting glycogen synthase kinase 3 (GSK3) such as CHIR99021 as suppressors of TA transcription in MCC cells. Involvement of GSK3α and -β in the regulation of TA-expression was confirmed by combining GSK3A knockout with inducible GSK3B shRNA knockdown since double knockouts could not be generated. Finally, we demonstrate that CHIR99021 exhibits in vivo antitumor activity in an MCC xenograft mouse model suggesting GSK3 inhibitors as potential therapeutics for the treatment of MCC in the future. Highlights: Proliferation of Merkel cell polyomavirus-positive Merkel cell carcinoma cells depends on virus-encoded T antigen expression. We developed an assay to identify compounds inhibiting Merkel cell carcinoma (MCC) cell growth by repressing TA expression. Applying this technique we identified compounds targeting GSK3 as suppressors of T antigen (TA) transcription in MCC cells. Combining  GSK3A  knockout with inducible  GSK3B  shRNA knockdown confirms their involvement in TA-expression regulation. The GSK3 inhibitor CHIR99021 exhibits  in vivo  antitumor activity in an MCC xenograft mouse model.